Recurrent respiratory tract infections or acute otitis media were not a risk factor for vocabulary development in children at 13 and 24 months of age. (14th September 2018) - Nylund, Annette; Toivonen, Laura; Korpilahti, Pirjo; Kaljonen, Anne; Peltola, Ville; Rautakoski, Pirkko
Abstract: Aim: This study examined associations between recurrent respiratory tract infections (RTI) and acute otitis media (AOM) during the first one and two years of life and vocabulary size at 13 and 24 months of age. Methods: We studied 646 children born between January 2008 and April 2010 and followed up from birth to two years of age with daily diary and study clinic visits during RTIs and AOM. The families were recruited from maternity health care clinics or delivery wards in south‐west Finland. Parents completed the MacArthur Communicative Development Inventory at 13 and 24 months, and the vocabularies of children with high rates of RTIs or AOM were compared to children without recurrent issues. Results: Of the 646 children, 9.6% had recurrent RTIs and 9.9% had recurrent AOM from 0 to 24 months. Children with high rates of RTIs or AOM did not have smaller vocabularies than children without recurrent RTIs or AOM. Girls had larger vocabularies and higher parental socioeconomic status was associated with a larger expressive vocabulary at 24 months. Conclusion: The child's gender and parental socioeconomic status played a more critical role in vocabulary development in the first two years than a high burden of RTIs or AOM.